Studi Kasus Kehamilan Risiko Tinggi Ketuban Pecah Dini di RSUD Sukoharjo - Riska Andriani; Tutik Yuliyanti - Poltekkes Bhakti Mulia Sukoharjo (Unit Penelitian dan Pengabdian Masyarakat Politeknik Kesehatan Bhakti Mulial, 2016)
From diagnosaâ€™s writer stack the plan of action andÂ implementation nursing. After doing upbringing nursing during 3x24 hours getting evaluation result for diagnose painful acute, and riks of infection is resolved.Keyword: nursing care, premature rupture of membrane